2015
DOI: 10.1128/aem.00239-15
|View full text |Cite|
|
Sign up to set email alerts
|

Polyphenolic Extract from Maple Syrup Potentiates Antibiotic Susceptibility and Reduces Biofilm Formation of Pathogenic Bacteria

Abstract: Phenolic compounds are believed to be promising candidates as complementary therapeutics. Maple syrup, prepared by concentrating the sap from the North American maple tree, is a rich source of natural and process-derived phenolic compounds. In this work, we report the antimicrobial activity of a phenolic-rich maple syrup extract (PRMSE). PRMSE exhibited antimicrobial activity as well as strong synergistic interaction with selected antibiotics against Gram-negative clinical strains of Escherichia coli, Proteus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 58 publications
1
47
0
Order By: Relevance
“…The transcriptome analysis revealed that PMRSE effectively repressed multiple drug resistance genes and genes associated with motility, adhesion and biofilm formation (Maisuria et al . ).…”
Section: Therapeuticsmentioning
confidence: 97%
“…The transcriptome analysis revealed that PMRSE effectively repressed multiple drug resistance genes and genes associated with motility, adhesion and biofilm formation (Maisuria et al . ).…”
Section: Therapeuticsmentioning
confidence: 97%
“…[67] An overnight-grown culture of each strain was diluted 1:100 in MHB-II broth to a final volume of 10 mL and was grown to an OD 600 of 0.8-1.0 (at 37 °C, 150 rpm). [67] An overnight-grown culture of each strain was diluted 1:100 in MHB-II broth to a final volume of 10 mL and was grown to an OD 600 of 0.8-1.0 (at 37 °C, 150 rpm).…”
Section: Methodsmentioning
confidence: 99%
“…Cumin demonstrated antimicrobial activity on its own and also resistance modulation properties against MRSA by inhibiting LmrS efflux pump [ 155 ]. Plant molecules inhibiting the ethidium bromide efflux pump (EtBr) have also been found: 1â€Č-S-1â€Č-acetoxyeugenol acetate inhibits it in Mycobacterium smegmatis [ 165 ], catechol and catharanthine inhibits it in P. aeruginosa [ 166 , 167 ] and galotannins inhibit it in MDR uropathogenic E. coli [ 168 ]. The Yojl efflux pump of MDR E. coli has been shown to be inhibited by molecules such as 4-hydroxy—tetralone, ursolic acid and its derivatives [ 169 ] and lysergol [ 170 ].…”
Section: Resultsmentioning
confidence: 99%